Legal Protection of Witnesses and Reporters in Revealing Narcotics Case by Pekanbaru City Police Resort - Khairani Miftahul Jannah (Indonesian Journal of Economics, Social, and Humanities, 2021)
Human life is inseparable from the problems to overcome this we need a rule that can prevent and impose sanctions on people who do things that are not in accordance with applicable norms or ethics. The law governing the protection of witnesses and victims as stated in the state sheet which is the Republic of Indonesia Law No. 31 of 2014 concerning Protection of Witnesses and Victims. During this time many criminal cases have never been touched by the legal process. The purpose of this thesis is finding out the legal protection of witnesses and reporters in revealing narcotics criminal acts by the Pekanbaru City Police and know the effort to overcome the legal protection barriers to witnesses and reporters in revealing criminal acts by the Pekanbaru City Police. This type of research can be classified with research classified into sociological juridical research where the research examines the effectiveness of the law that is in force. From the research result, it is found that, first in protecting the rights of witnesses and victims, the government established an institution called the Witness and Victim Protection Agency (LPSK). Protection of witnesses and/or victims is declared to remain valid as long as it does not conflict with Article 44 of Law Number 13 year 2006 concerning protection of witnesses and victims. Second, the obstacles that occur are physical and psychological threats as well as criminalization efforts againts witnesses and victims or their families that make them afraid to give testimony before the court.